Potentials and challenges in carrying out educational workshops with adolescents - Renata Soares Morais, Maria Adelane Monteiro da Silva, Rebeca Sales Viana, Deline Lopes Moraes, Camila Martins de Oliveira (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v6i2.5752